Genetic Variants in Double-Strand Break Repair Pathway Genes to Predict Platinum-Based Chemotherapy Prognosis in Patients With Lung Cancer - Liu, Jun-Yan; Zou, Ting; Yin, Ji-Ye; Wang, Zhan; Liu, Chong; Huang, Han-Xue; Ding, Fei-Xiang; Lei, Meng-Rong; Wang, Ying; Liu, Min; Liu, Zhao-Qian; Tan, Li-Ming; et al. (Frontiers in Pharmacology, 2022)
Objective: The purpose of this study was to investigate the associations of genetic variants in double-strand break (DSB) repair pathway genes with prognosis in patients with lung cancer treated with platinum-based chemotherapy. Methods: Three hundred ninety-nine patients with lung cancer who received platinum-based chemotherapy for at least two cycles were included in this study. A total of 35 single nucleotide polymorphisms (SNPs) in DSB repair, base excision repair (BER), and nucleotide excision repair (NER) repair pathway genes were genotyped, and were used to evaluate the overall survival (OS) and the progression-free survival (PFS) of patients who received platinum-based chemotherapy using Cox proportional hazard models. Results: The PFS of patients who carried the MAD2L2 rs746218 GG genotype was shorter than that in patients with the AG or AA genotypes (recessive model: p = 0.039, OR = 5.31, 95% CI = 1.09–25.93). Patients with the TT or GT genotypes of TNFRSF1A rs4149570 had shorter OS times than those with the GG genotype (dominant model: p = 0.030, OR = 0.57, 95% CI = 0.34–0.95). We also investigated the influence of age, gender, histology, smoking, stage, and metastasis in association between SNPs and OS or PFS in patients with lung cancer. DNA repair gene SNPs were significantly associated with PFS and OS in the subgroup analyses. Conclusion: Our study showed that variants in MAD2L2 rs746218 and TNFRSF1A rs4149570 were associated with shorter PFS or OS in patients with lung cancer who received platinum-based chemotherapy. These variants may be novel biomarkers for the prediction of prognosis of patients with lung cancer who receive platinum-based chemotherapy.